2014
DOI: 10.1021/ja411117y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Mesoporous Single-Crystalline Zeolite Beta Synthesized Using a Nonsurfactant Cationic Polymer as a Dual-Function Template

Abstract: Mesoporous zeolites are useful solid catalysts for conversion of bulky molecules because they offer fast mass transfer along with size and shape selectivity. We report here the successful synthesis of mesoporous aluminosilicate zeolite Beta from a commercial cationic polymer that acts as a dual-function template to generate zeolitic micropores and mesopores simultaneously. This is the first demonstration of a single nonsurfactant polymer acting as such a template. Using high-resolution electron microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
188
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 276 publications
(207 citation statements)
references
References 72 publications
8
188
1
Order By: Relevance
“…For example, we recently reported that a non-surfactant cationic polymer can act as a dual template to synthesize hierarchical zeolite Beta. 28 The obtained material (Beta-MS) featured remarkable mesoporosity, single crystallinity, excellent stability, and superior catalytic activity over conventional zeolite Beta in several liquid-phase reactions. Although there is a bulk of evidence for the superior catalytic properties of hierarchical zeolites, a systematic 4 comparison between a hierarchical zeolite and its bulk (non-mesoporous) counterpart for a particular reaction on the basis of detailed catalyst characterization and a careful analysis of the full products is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…For example, we recently reported that a non-surfactant cationic polymer can act as a dual template to synthesize hierarchical zeolite Beta. 28 The obtained material (Beta-MS) featured remarkable mesoporosity, single crystallinity, excellent stability, and superior catalytic activity over conventional zeolite Beta in several liquid-phase reactions. Although there is a bulk of evidence for the superior catalytic properties of hierarchical zeolites, a systematic 4 comparison between a hierarchical zeolite and its bulk (non-mesoporous) counterpart for a particular reaction on the basis of detailed catalyst characterization and a careful analysis of the full products is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Hard template route using carbon blacks 8 , soft template using organosilanes 9 , cationic polymers 10 , bifunctional structure directing agent 11 , as well as postsynthetic desilication 12 routes have been established. Several merits stems from prompted mass transport for instance, high activity, occasional high primary product selectivity, improved large molecule accessibility, as well as longer lifetimes, have been achieved by replacing conventional zeolites with HPZs 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The acid sites were probed by IR spectroscopy of adsorbed pyridine (Fig. [13] The B-MS sample had a high external surface area (399 m 2 ·g -1 ). The results revealed that the Brønsted acid site of B-MS was 0.09 mmol·g -1 , which was lower than that of B-20 (0.20 mmol·g -1 ) and B-26 (0.18mmol·g -1 ).…”
Section: Introductionmentioning
confidence: 99%